Effect of Maggot Meal (Hermetia illucens) Inclusion in Diets Containing Senduduk Leaves (Melastoma malabathricum L.) on Egg Production Performance of Quails from Start to Peak Production): Pengaruh Penggunaan Tepung Maggot (Hermentia illucens) pada Ransum yang Mengandung Daun Senduduk (Melastoma malabathricum L.) terhadap Performa Produksi Telur Puyuh pada Awal Produksi sampai Puncak Produksi - Agiel Tulus Widyananto; Kususiyah Kususiyah; Warnoto Warnoto; Anggun Marisa (BPFP Universitas Bengkulu, 2026)
This study aimed to evaluate the effect of maggot meal inclusion in diets containing senduduk leaves on the egg production performance of quails from the onset of laying to peak production. The basal diet included 4% senduduk leaves in all treatments. A completely randomized design was applied with four treatments, five replications, and eight quails per replicate. The treatments consisted of different levels of maggot meal: 0% (P0), 5% (P1), 10% (P2), and 15% (P3). Measured variables included feed intake, egg production, egg weight, egg mass, and feed conversion ratio. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test for significant effects. The results showed that maggot meal inclusion had no significant effect (P>0.05) on feed intake, which ranged from 143.19 to 145.49 g/bird/week. However, it significantly affected (P<0.01) egg production, egg weight, egg mass, and feed conversion ratio. Egg production in P0 (2.59 eggs/bird/week) was significantly lower than in P1 (4.04), P2 (3.50), and P3 (4.66). Similarly, egg weight and egg mass were significantly lower in P0 compared to other treatments. Feed conversion ratio was significantly higher in P0 (6.8) than in P1 (3.61), P2 (4.14), and P3 (2.96). In conclusion, maggot meal can be included up to 15% in diets containing 4% senduduk leaves to partially replace concentrate without reducing quail egg production performance.